Breast cancer in South-Eastern European countries since 2000: Rising incidence and decreasing mortality at young and middle ages. (September 2017) - ,; Agius, Dominic; Coza, Daniela; Gheorghiu, Raluca; Diba, Chakameh Safaei; Pavlou, Pavlos; Demetriou, Anna; Eser, Sultan; Gavrić, Živana; Primic-Žakelj, Maja; Ryzhov, Anton; Sekerija, Mario; et al.
Abstract: Background: Marked variations exist in the incidence and mortality trends of major cancers in South-Eastern European (SEE) countries which have now been detailed by age for breast cancer (BC) to seek clues for improvement. Methods: We brought together and analysed data from 14 cancer registries (CRs), situated in SEE countries or directly adjacent. Age-standardised rate at world standard (ASRw) and truncated incidence and mortality rates during 2000–2010 by year, and for four age groups, were calculated. Average annual percentage change of rates was estimated using Joinpoint regression. Results: Annual incidence rates increased significantly in countries and age groups, by 2–4% (15–39 years), 2–5% (40–49), 1–4% (50–69) and 1–6% (at 70+). Mortality rates decreased significantly in all age-groups in most countries, but increased up to 5% annually above age 55 in Ukraine, Serbia, Moldova and Cyprus. The BC data quality was evaluated by internationally agreed indicators which appeared suboptimal for Moldova, Bosnia and Herzegovina and Romania. Conclusion: The observed variations of incidence trends reflect the influence of risk factors, as well as levels of early detection activities (screening). While mortality rates were mostly decreasing, probably due to improved cancer care and introduction of more effective systemic treatment regimens, the worrying increasing mortality trends in the 55-plus age groups in some countries have to be addressed by health professionals and policymakers. In order to assess and monitor the effects of cancer control activities in the region, the CRs need substantial investments. Highlights: Breast cancer incidence and mortality trends in South-Eastern Europe have been detailed by age. The breast cancer data quality was evaluated by internationally agreed indicators. Annual incidence rates increased significantly in countries and age groups. Mortality rates decreased in most countries, but increased above age 55 in some of them. Cancer registries in the region have a potential to expand their role in breast cancer control.